2010
DOI: 10.1002/app.31769
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of nanofiltration for the advanced treatment of landfill leachate

Abstract: Landfill leachates are generated from municipal solid waste landfills under the action of water percolating through the landfilled waste. A treatment system using a combined membrane engineering process was developed to effectively treat the landfill leachate in the Dahanzhuang sanitary landfill (Tianjin, China). The process combines a membrane bioreactor (MBR) and nanofiltration (NF) technology to treat the leachate. The results indicate that the NF system, including the hollow-fiber NF membrane, is an approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Pressure-driven membrane process (microfiltration, ultrafiltration, nanofiltration, reverse osmosis (RO)) is one of the most promising and efficient methods for landfill leachate treatment (Li et al, , 2010. Large volume of concentrated leachate is generated from the pressure-driven membrane process separating into a purified permeate fraction and a concentrated retentate fraction, especially during the RO process.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure-driven membrane process (microfiltration, ultrafiltration, nanofiltration, reverse osmosis (RO)) is one of the most promising and efficient methods for landfill leachate treatment (Li et al, , 2010. Large volume of concentrated leachate is generated from the pressure-driven membrane process separating into a purified permeate fraction and a concentrated retentate fraction, especially during the RO process.…”
Section: Introductionmentioning
confidence: 99%
“…The NF process proved to be effective in COD removal, and was able to frame the treated effluent within this parameter according to current Brazilian laws (180 mg/L of COD or removal >55%). The literature reports the possibility of applying a subsequent NF unit to MBRs treating leachate [27,28]. Jakopović et al [29] used NF membrane on the MBR effluent, and observed an improvement in COD removal efficiency from 23% (MBR alone) to 92% (MBR associated with NF).…”
Section: Nanofiltrationmentioning
confidence: 99%
“…This necessitates the adoption of a pre-treatment and/or post-treatment in MBR systems to ensure good effluent quality (Table 2), especially with increasingly stringent discharge standards. In this context, various technologies have been explored with different levels of success as a polishing treatment for leachate effluent from MBR systems such as Nanofiltration Ince et al 2010Ince et al , 2013Li et al 2010;Jakopović et al 2008;Robinson 2007;Hua and Zhang 2012), Microfiltration (Ince et al 2010), Electrochemical Oxidation (Feki et al 2009;Aloui et al 2009), Reverse Osmosis Ahn et al 2002;Bohdziewicz et al 2008;Hasar et al 2009b;Mahmoudkhani et al 2012;Zhang et al 2013;Insel et al 2013 (Akgul et al 2013). Note that the MBR itself was examined as a post-treatment for the effluent of UASB treating medium aged leachate, which reduced the variation in UASB effluent quality (Akkaya et al 2010) and for the effluent of SBR treating compost leachate (Hashemi et al 2015) whereby the FS module showed superior effluent quality namely in terms of BOD and COD.…”
Section: Pretreatment and Post-treatmentmentioning
confidence: 99%